ICT skill among Labuan’s SMEs: issues and challenges - Mohd Zulkifli Muhammad; Say Leng Goh; Tamrin Amboala; Nasrul Hisyam Nor Muhamad (2012)
The rapid growth of ICT presents both perpetual opportunities and challenges to SMEs. ICT serves as a competitive tool for SMEs provided they have the necessary skills and knowledge to embrace it. However, due to the growth characteristic of ICT, skills shortages will remain as an issue haunting SMEs. Continuous staff training is the way out, however many SMEs are reluctant to train their workforce. Issues and barriers pertaining to skills development were reviewed by referencing previous studies undertaken. The paper highlights ICT skill challenges facing SMEs in Labuan. Among the focus of investigation are; usage of computers, current training provision, awareness and attitudes toward ICT and training, areas for ICT training and support needs. The paper concludes by outlining several suggestions to improve on ICT skills development among SMEs in Labuan.